Multi-Order Brain Functional Connectivity Network-Based Machine Learning Method for Recognition of Delayed Neurocognitive Recovery in Older Adults Undergoing Non-cardiac Surgery - Wu, Guoqing; Jiang, Zhaoshun; Cai, Yuxi; Zhang, Xixue; Lv, Yating; Li, Shihong; Lin, Guangwu; Bao, Zhijun; Liu, Songbin; Gu, Weidong (Frontiers in Neuroscience, 2021)
Objectives: Delayed neurocognitive recovery (DNR) seriously affects the postoperative recovery of elderly surgical patients, but there is still a lack of effective methods to recognize high-risk patients with DNR. This study proposed a machine learning method based on multi-order brain functional connectivity (FC) network to recognize DNR. Method: 74 patients who completed assessments were included in this study, in which 16/74 (21.6%) had DNR following surgery. Based on resting-state functional magnetic resonance imaging (rs-fMRI), we first constructed low-order FC networks of 90 brain regions by calculating the correlation of brain region signal changing in the time dimension. Then we established high-order FC networks by calculating correlations among each pair of brain regions. Afterwards, we built sparse representation-based machine learning model to recognize DNR on the extracted multi-order FC network features. Finally, an independent testing was conducted to validate the established recognition model. Results: 390 features of FC networks were finally extracted to identify DNR. After performing the Independent-Samples T Test between these features and the categories, 15 features showed statistical differences (P<0.05), and 3 features had significant statistical differences (P<0.01). By comparing DNR and non-DNR patients' brain region connection matrix, it is found that there are more connections among brain regions in DNR patients than that in non-DNR patients. For machine learning recognition model based on multi-feature combination, the area under the receiver operating characteristic curve (AUC), accuracy, sensitivity, and specificity of the classifier reached 95.61%, 92.00%, 66.67%, and 100.00 %, respectively. Conclusion: This study not only reveals the significance of preoperative rs-fMRI in recognizing postoperative DNR in elderly patients, but also establishes a promising machine learning method to recognize DNR.